Further Education (FE) to Higher Education (HE) Progression Pathways: (European Journal of Teaching and Education, 2023)
Equity of access to higher education (HE) has been a priority for the Irish Government over the last fifteen years. Since 2005, the Higher Education Authority (HEA) in Ireland has introduced three successive national strategic plans for equity of access, which demonstrates its importance in HE policy. The aim of these initiatives is to improve equity of access, participation and success in HE for disadvantaged students. The findings generated from the third of these strategic plans, indicate that although some progress has been made to support this integration from further education (FE) to HE, challenges remain with an acknowledgement that there is a need to establish transparent supporting structures for building coherent pathways from FE to HE. Higher-level qualifications are now a common expectation among the general population and in industry, reflecting increased ambition, labour market demand for higher-level skills, and the need to continually upskill and/or reskill. The objective of this empirical investigation is to identify the perceived barriers preventing students of FE from progressing to HE in Ireland. Like others who have investigated this topic this investigation adopted an interpretivist approach to enquiry and a case study methodological approach. Primary data was generated from in depth focus groups and qualitative surveys. Data was analysed using thematic analysis. The preliminary findings of the first phase of this investigation illustrate that student transition from FE to HE is multidimensional. Findings have supported the development of a draft Transitions Framework, which is currently being piloted with case study students. The ultimate goal is to pursue the effective implementation of the Transitions Framework.